Calcium ion-triggered liquid-liquid phase separation of silk fibroin and spinning through acidification and shear stress - Sejun Yang; Yeonwoo Yu; Seonghyeon Jo; Yehee Lee; Seojin Son; Ki Hoon Lee (Nature Communications)
Abstract Many studies try to comprehend and replicate the natural silk spinning process due to its energy-efficient and eco-friendly process. In contrast to spider silk, the mechanisms of how silkworm silk fibroin (SF) undergoes liquid–liquid phase separation (LLPS) concerning the various environmental factors in the silk glands or how the SF coacervates transform into fibers remain unexplored. Here, we show that calcium ions, among the most abundant metal ions inside the silk glands, induce LLPS of SF under macromolecular crowded conditions by increasing both hydrophobic and electrostatic interactions between SF. Furthermore, SF coacervates assemble and further develop into fibrils under acidification and shear force. Finally, we prepare SF fiber using a pultrusion-based dry spinning, mirroring the natural silk spinning system. Unlike previous artificial spinning methods requiring concentrated solutions or harsh solvents, our process uses a less concentrated aqueous SF solution and minimal shear force, offering a biomimetic approach to fiber production.